The Influence of Service Quality, Promotion, Store Atmosphere, and Subjective Norms on Customer Loyalty - Silvester Ade Boruk; Sugiyanto Sugiyanto (The Future of Education Journal, 2026)
The increasing competition in the barbershop business requires every business owner to maintain customer loyalty by improving service quality, implementing effective promotion strategies, creating a comfortable store atmosphere, and considering social influences. This study aims to analyze the influence of service quality, promotion, store atmosphere, and subjective norms on customer loyalty at Barbershop D1 in South Tangerang. Methodology: This research employed a quantitative approach, using questionnaires distributed to 100 respondents who are customers of Barbershop D1 and residents of the South Tangerang area. The data were analyzed using multiple linear regression analysis to test the partial and simultaneous effects between variables. Findings: The results indicate that service quality, promotion, store atmosphere, and subjective norms have a positive and significant effect on customer loyalty, both partially and simultaneously. This implies that better service quality, more effective promotions, a more comfortable store atmosphere, and stronger social influence lead to higher customer loyalty toward Barbershop D1, South Tangerang.